The effects of different mechanisms on the development of post-ERCP pancreatitis in an ERCP model in rats - Süleyman BOZKURT,; Ali Güner,; Hüseyin KADIOĞLU,; Can KEÇE,; Erhan REİS,; Halil COŞKUN, (Turkish Journal of Gastroenterology, 2019)
-